A Fair User Selection Algorithm for Multi-User Massive MIMO System - Dhoni Putra Setiawan; Hua-An Zhao (Department of Electrical Engineering ITS and FORTEI, 2018)
Massive Multiple-input Multiple-output (Massive MIMO) system is one of the most potential candidates for the fifth-generation wireless communication. Massive-MIMO system employs a very large number of antennas which could easily reach more than a thousand antennas in the future. Instead of using an omni directional antenna which is a very popular base station antenna nowadays, massive-MIMO uses its large number of antennas to create multiple smaller beams which are transmitted directly into the intended receivers. In this paper, we develop a user-scheduling technique for Multi-user Massive-MIMO system called Fair-CDUS which is developed from charcoal distance-based user selection (CDUS) technique. Fair-CDUS aims to give more fairness to users in term of selection frequency and at the same time could maintain the total throughput performance. Some experimental scenarios with a different number of beams and a different number of receiving antenna are presented in this paper. We believe this proposed method could be a potential method to be used in Multi-user Massive-MIMO system. Keyword: Massive-MIMO, Multi-user, 5G, User Scheduling, Fairness